How Large Are Global Fossil Fuel Subsidies?. (March 2017) - Coady, David; Parry, Ian; Sears, Louis; Shang, Baoping
Highlights: Fossil fuel subsidies are large, amounting to 6.5% of global GDP in 2015. Mispricing from a domestic perspective accounts for the bulk of the subsidy. Coal subsidies account for the largest part (about half) of global subsidies. In absolute terms, subsidies are highly concentrated in a few large countries. The environmental, fiscal, and welfare gains from subsidy reform are substantial. Summary: This paper estimates fossil fuel subsidies and the economic and environmental benefits from reforming them, focusing mostly on a broad notion of subsidies arising when consumer prices are below supply costs plus environmental costs and general consumption taxes. Estimated subsidies are 4.9 trillion worldwide in 2013 and 5.3 trillion in 2015 (6.5% of global GDP in both years). Undercharging for global warming accounts for 22% of the subsidy in 2013, air pollution 46%, broader vehicle externalities 13%, supply costs 11%, and general consumer taxes 8%. China was the biggest subsidizer in 2013 (1.8 trillion), followed by the United States (0.6 trillion), and Russia, the European Union, and India (each with about 0.3 trillion). Eliminating subsidies would have reduced global carbon emissions in 2013 by 21% and fossil fuel air pollution deaths 55%, while raising revenue of 4%, and social welfare by 2.2%, of global GDP.